Gambaran Keluhan Carpal Tunnel Syndrome (CTS) pada Pekerja Pengguna Komputer - Furti Okliantoni Pratiwi; Herlina; Wasisto Utomo (HEALTH CARE : JURNAL KESEHATAN, 2022)
Introduction: Carpal Tunnel Syndrome (CTS) is one such labor related cases of illness that pertain to the upper extremities and concern for long duration use of the wrist. Flections and repetitive finger extentions (repetitive work) in the long use of a mouse or keyboard in the wrong hand position are among the causes of CTS in computer user workers. Purpose: Research aims to identify CTS complaints images on computer user workers. Method: The method used is a simple descriptive research design with a sectional cross approach. Research sample number 65 respondents taken through sampling purposive techniques. The measuring tool used is a BCTS questionnaire. The data analysis used is a univariate analysis. Result: Research indicates that the preferred incidence of CTS of the respondents was about 43 people (66,2%) and the number of CTS complaints it had was the growing pains of 31 (47,7%). Conclusion: Most computer user workers have a CTS complaint. This should be of concern to computer user workers in order to make prevention and treatment to reduce complaints so as not to interfere with work productivity.